Gender and generation gaps in government organization: does it affect work engagement? - Gugup Kismono; Utilithia Banguningsih Hanggarawati (Jurnal Siasat Bisnis, 2022)
Purpose: This research proposed to evaluate the differences between generations and gender work engagement. This evaluation is strategically needed to clarify the debate related to the issue of work engagement. The clarification based on research findings involving respondents from different context is necessary to improve ecological validity. It is also important since the evidence obtained through this research is useful for improving the effectiveness of human resources policies.Design/Methodology/Approach: The data were collected through self-administered questionnaire involving 128 respondents from a specific context of government organization. There were 17 items used to represent work engagement. The measurement was adapted from UWES-17. ANOVA and independent sample t-test were conducted to test the influence of generations and gender on the total of work engagement and its three dimensions.Findings: Results showed that generation and gender influence work engagement. Baby Boomers indicated the strongest work engagement. Generation Y showed the lowest work engagement. Men exhibited higher work engagement than women. However, further evaluation on the dimensions of work engagement showed interesting findings. Baby Boomers did not significantly differ from their counterpart of generation X on any dimensions. Generation X consistently differed from generation Y in all dimensions. Regarding gender and the dimensions of work engagement, only absorption showed insignificant different. In general, the findings of this research was align with the theory of social exchange as well as antithesis of burnout.Research Limitation/Implications: The data were collected from the government officials. It is limited that it may not capture the employees’ characteristics from business organization. Generalization may also be limited. However, this specific context may offer a valuable perspective related to the situation in which seniority is important point in considering career decision made by the organization. In addition, the measurement used in this research adapted from UWES-17. Research showed that different work engagement measurement applied in diverse culture may result in inconsistent findings. A comprehensive research was necessary to evaluate the measurement that was relatively free from cultural influences.Practical Implications: This research offered an interesting recommendation in relation with organizational policies to improve work engagement and its dimensions. Based on this research findings, organizations may consider emphasizing on human resources policies which was suitable for generation Y to improve work engagement. Moreover, work-life balance to improve the level of women work engagement was also recommended.Originality/Value: This research was contributed to evaluate the impact of generations and gender on work engagement and its dimensions. Research involving specific context as government officials was rare. The result may be crucial to avoid developing organizational policies that were based on research findings that came from irrelevant contexts.